Norway : Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
This Selected Issues paper of Norway presents a cyclical indicator of fiscal policy at the general government level, and provides an updated assessment of the long-term fiscal position based on the future profile of the State Petroleum Fund (SPF). The study focuses on structural changes needed and prospects for privatization of state assets in the telecommunications and petroleum sectors. The paper analyzes the key issues in the Norwegian financial sector, outlines recent financial developments and banking soundness indicators, and also assesses the financial policy framework.